Search for the Anomalous Interactions of Up-Type Heavy Quarks in γγ Collision at the LHC - M. Köksal; S. C. İnan (Advances in High Energy Physics)
We investigate the anomalous interactions of heavy up-type quark t′ in a γγ collision at the LHC. We have obtained 95% confidence level (CL) limit of t′qγ (q=u,c) anomalous coupling by taking into account three forward detector acceptances: 0.0015<ξ<0.15, 0.0015<ξ<0.5, and 0.1<ξ<0.5.